ПЕРШИЙ ВИПАДОК «ЦВІТІННЯ» NODULARIA SPUMIGENA MERTENS EX BORN. ET FLAH. У ЧОРНОМУ МОРІ - Александров, Б. Г.; Нестерова, Д. А.; Теренько, Л. М. (Marine Ecological Journal, 2023)
First case of Nodularia spumigena blooming in the Black Sea.